Comparison of functional outcome in fixed bearing versus mobile bearing implant designs in total knee arthroplasty - Sajjad Ali B; Arun Raja C J; Kathiravan Rajendran (Journal of the Bulgarian Orthopaedics and Trauma Association)
Introduction:Total Knee Arthroplasty (TKA) is a common surgical procedure aimed at relieving pain and restoring function in advanced knee arthritis. TKA implants are categorized into fixed-bearing and mobile-bearing designs based on polyethylene bearing mobility. Fixed-bearing implants, where the tibial insert is fixed to the tray, show excellent outcomes in older, less active patients. However, issues such as patellofemoral articulation, polyethylene wear, and osteolysis remain. Mobile-bearing designs address these concerns by allowing insert movement, improving articulation conformity, and reducing stress on the tibial interface. This study compares the functional outcomes of fixed- and mobile-bearing TKA designs.Objectives:a) Assessing functional outcomes using the Knee Society Knee Score System (KSKS).b) Comparing postoperative range of motion (ROM) between the two implant designs.Methodology:This comparative study, conducted at Kovai Medical Center and Hospital, included 73 patients (90 knees) who underwent TKA . The fixed-bearing design used a cruciate-substituting posterior-stabilized (PS) prosthesis, while the mobile-bearing design featured a rotating platform (RPF) prosthesis from the same manufacturer. Functional outcomes were assessed using KSKS, WOMAC, and ROM measurements. Most surgeries utilized a medial parapatellar approach, with a lateral approach for select valgus knees. Posterior cruciate ligament (PCL) resection was performed when necessary.Results:Both the fixed-bearing (PS) and mobile-bearing (RPF) cohorts exhibited significant postoperative improvements in ROM and knee scores compared to baseline values. The mean postoperative ROM was recorded as 100.06° in the PS group and 99.63° in the RPF group. The mean improvement in Knee Score was 66.72 in the PS group and 69.85 in the RPF group. Conclusion:This study concludes that functional outcomes following TKA do not exhibit a statistically significant variation between fixed- and mobile-bearing implant designs. Instead, the attainment of optimal surgical outcomes is predominantly influenced by meticulous tissue balancing and surgical technique.